2014
DOI: 10.2337/db13-1864
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Advanced Glycation End Products Are Associated With Incident Cardiovascular Events in Individuals With Type 2 Diabetes: A Case-Cohort Study With a Median Follow-up of 10 Years (EPIC-NL)

Abstract: Experimental data suggest a role for advanced glycation end products (AGEs) in cardiovascular disease (CVD), particularly in type 2 diabetes (T2DM). However, epidemiological evidence of an association between high plasma AGEs and increased cardiovascular risk remains inconclusive. Therefore, in a case-cohort study comprising 134 cardiovascular case subjects and a random subcohort of 218 individuals (including 65 cardiovascular case subjects), all with T2DM and nested in the European Prospective Investigation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
104
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(115 citation statements)
references
References 39 publications
8
104
2
1
Order By: Relevance
“…Connections to vascular diseases, diabetic complications and diabetic neuropathy, and amyloid-type neurodegenerative disease, among other areas, are being investigated (13,15,118). In the area of vascular disease and diabetes, a recent study has reported that increased MG derived AGE appear to be associated with an increased risk of cardiovascular events in type 2 diabetic patients (119). Post-translationally glycated proteins are thought to exert their effects on cells by a receptor-mediated pathway that includes their interaction with a receptor recognizing AGE-modified proteins.…”
Section: Advanced Glycation End-products (Age) and The Dicarbonyl Promentioning
confidence: 99%
“…Connections to vascular diseases, diabetic complications and diabetic neuropathy, and amyloid-type neurodegenerative disease, among other areas, are being investigated (13,15,118). In the area of vascular disease and diabetes, a recent study has reported that increased MG derived AGE appear to be associated with an increased risk of cardiovascular events in type 2 diabetic patients (119). Post-translationally glycated proteins are thought to exert their effects on cells by a receptor-mediated pathway that includes their interaction with a receptor recognizing AGE-modified proteins.…”
Section: Advanced Glycation End-products (Age) and The Dicarbonyl Promentioning
confidence: 99%
“…In addition, higher concentrations were seen in (industrially) processed foods from animal products such as frankfurters, bacon and powdered egg whites, compared with the unprocessed forms (75) . It is well-known that high circulating advanced glycation end products levels are associated with adverse outcomes in diabetes patients (76)(77)(78) , but so far no epidemiological study has evaluated whether dietary advanced glycation end products intake or circulating levels are associated with incident type-2 diabetes.…”
Section: Type-2 Diabetes Mellitusmentioning
confidence: 99%
“…This was in reasonable agreement with data described in literature [36][37][38][39][40][41] . The described method is suitable for studying AGEs in several different human and animal studies [42][43][44][45][46][47][48][49] and is a strong tool to investigate the putative effects of AGEs in the pathophysiology of different diseases.…”
Section: Discussionmentioning
confidence: 99%
“…AGEs, in our body, can also originate from exogenous sources such as diet and smoking 49,50 . AGEs in foods are formed rapidly during processing at high temperatures, such as grilling, frying, baking or roasting 49,51,52 .…”
mentioning
confidence: 99%
See 1 more Smart Citation